2019
DOI: 10.3390/app9040723
|View full text |Cite
|
Sign up to set email alerts
|

Low-Voltage Solid-State DC Breaker for Fault Protection Applications in Isolated DC Microgrid Cluster

Abstract: Due to the interconnected scheme of multiple components, such as distributed generators, storage systems, and loads through converters to a common bus in DC microgrids, the possibility of fault occurrence is increasing significantly. Meanwhile, due to the huge and rapid increase of short-circuit currents, the development of a small- and large-scale DC system requires a reliable and fast protection system to ensure fault clearance and maintain safety for the rest of the system. Thus, fault protection has been f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…SSCBs can be damaged due to overvoltage of the inductive components of the system, hence the importance of reducing this voltage for the safety of the device. To protect the solid-state switch from overvoltage at the moment of opening, additional elements are required, such as resistors, capacitors, diode (RCD) Snubber Circuits, metal oxide varistors (MOV), and freewheeling diodes [10,72]. In the Ref.…”
Section: Sscbs General Descriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…SSCBs can be damaged due to overvoltage of the inductive components of the system, hence the importance of reducing this voltage for the safety of the device. To protect the solid-state switch from overvoltage at the moment of opening, additional elements are required, such as resistors, capacitors, diode (RCD) Snubber Circuits, metal oxide varistors (MOV), and freewheeling diodes [10,72]. In the Ref.…”
Section: Sscbs General Descriptionmentioning
confidence: 99%
“…In the Ref. [10], a suitable IGBT for low-voltage (around 400 V) fault protection of a DCMG was proposed. The simulation results showed that the SSCB acted reliably and the fault current dropped to zero within 15 µs until the fault was removed from the system and reconnected within 8 µs, while the rest of the system continued to operate normally.…”
Section: Recent Developments Of Sscbsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Table 1, the focus of the reported studies on DC MG clusters is summarized to highlight the lack of enough investigations on the protection of these systems. In [22], an LV DC circuit breaker (CB) has been suggested for the protection of autonomous DC MG clusters. However, the interlink converter between individual DC MGs was not discussed in the paper.…”
Section: Introductionmentioning
confidence: 99%